Endgame : inside the impeachment of Donald J. Trump - Swalwell, Eric (2020)
How do you stop a rogue president? How do you protect our country from a man who lies, who obstructs justice, and who seeks to cheat with foreign powers to get reelected? Our constitution offers one remedy: impeachment. Thanks to the courageous actions of public servants who came forward to report his abuses of power, on December 18, 2019, President Donald J. Trump became just the third president in US history to be impeached by the House of Representatives. In Endgame, Congressman Eric Swalwell offers his personal account of his path to office and how he and his colleagues resisted, investigated, and impeached a corrupt president. After the shock of the 2016 election and Trump's inauguration (including the luncheon afterward), Swalwell, as a member of the House Permanent Select Committee on Intelligence and the House Judiciary Committee, quickly became involved in pushing back against Trump's outrageous actions as he sought to get to the bottom of foreign interference in our elections. But Republicans were in control of the investigation, and it became clear that taking back the House was essential. Swalwell takes readers inside Congress and through the impeachment process, from Trump's disgraceful phone call with the Ukrainian president, just one day after Robert Mueller testified to Congress, to caucus meetings and conversations with the Speaker to the bombshell public hearings and the historic vote, and then what followed next--the holding of the articles, the news of more possible witnesses, and the sham trial in the Senate. Endgame is fascinating, a gripping read by a unique witness to extraordinary events.